Sequence analysis of antimicrobial resistance genes in staphylococcus aureus in selected Southeast Asian countries - Giron, Genevieve D. (Animo Repository, 2023)
The increasing antimicrobial resistance of Staphylococcus aureus is a matter of concern in the medical community. Despite the usage of antimicrobials for the treatment of S. aureus infections, resistance is still steadily increasing, especially in Southeast Asia. In this study, a total of 654 S. aureus whole and partial genome and plasmid sequences were sourced from the National Center for Biotechnology Information and the European Nucleotide Archive databases. Using available bioinformatics pipeline such as the CGE (Center for Genomic Epidemiology) ResFinder 4.1, the strains were characterized based on the presence of antimicrobial resistance genes. Results showed that beta-lactam resistance (92%) was found to be the most commonly present among the strains, followed by macrolide-lincosamide-streptogramins (MLS) (44.2%) and tetracycline resistance genes (39.2%). The most prominent resistance gene discovered was blaZ, which was present in 440 (67.3%) strains, followed by mecA which was found in 218 (33.3%) strains, tet(K) in 168 (25.7%) strains, and erm(C) present in 176 (26.9%) strains. The calculated p-MAR indices showed that 316 (68.1%) strains possessed a p-MAR index ofS. aureus strains in Southeast Asia and this health issue must be addressed by each country. Keywords: Staphylococcus aureus, antimicrobial resistance, resistance genes, Potential Multi- antibiotic Resistance (p-MAR) index, multiple drug resistant